Influence of Mindfulness-Based Stress Reduction (MBSR) on Telomerase Activity in Women With Breast Cancer (BC). (October 2014) - Lengacher, Cecile A.; Reich, Richard R.; Kip, Kevin E.; Barta, Michelle; Ramesar, Sophia; Paterson, Carly L.; Moscoso, Manolete S.; Carranza, Irina; Budhrani, Pinky H.; Kim, Seung Joon; Park, Hyun Y.; Jacobsen, Paul B.; et al.
Mindfulness-based stress reduction (MBSR) reduces symptoms of depression, anxiety, and fear of recurrence among breast cancer (BC) survivors. However, the effects of MBSR (BC) on telomere length (TL) and telomerase activity (TA), known markers of cellular aging, psychological stress, and disease risk, are not known. This randomized, wait-listed, controlled study, nested within a larger trial, investigated the effects of MBSR (BC) on TL and TA. BC patients (142) with Stages 0–III cancer who had completed adjuvant treatment with radiation and/or chemotherapy at least 2 weeks prior to enrollment and within 2 years of completion of treatment with lumpectomy and/or mastectomy were randomly assigned to either a 6-week MBSR for BC program or a usual care. Assessments of TA and TL were obtained along with psychological measurements at baseline, 6 weeks, and 12 weeks after completing the MBSR(BC) program. The mean age of 142 participants was 55.3 years; 72% were non-Hispanic White; 78% had Stage I or II cancer; and 36% received both chemotherapy and radiation. In analyses adjusted for baseline TA and psychological status, TA increased steadily over 12 weeks in the MBSR(BC) group (approximately 17%) compared to essentially no increase in the control group (approximately 3%, p < .01). In contrast, no between-group difference was observed for TL ( p = .92). These results provide preliminary evidence that MBSR(BC) increases TA in peripheral blood mononuclear cells from BC patients and have implications for understanding how MBSR(BC) may extend cell longevity at the cellular level.